Proses Forgiveness Pada Perempuan Gen Z Pemaafan Masa Dewasa Awal Akibat Kekerasan di Masa Kecil - Aziza, Rifqa; Munawwaroh, Munawwaroh; Komalasari, Shanty (Universitas Negeri Surabaya, 2024)
This study aims to determine the process of forgiveness in early adulthood in gen z women who have experienced violence in their childhood. This research uses a qualitative approach with a case study method. Data were obtained from structured interviews. The participants in this study were two early adult women who had experienced violence in their childhood. By referring to the two dimensions of forgiviness, namely the intrapsychic and interpersonal dimensions. The results of this study show that both early adult female participants have successfully forgiven but are still processing towards total forgiveness. The first early adult female participant received a request from her mother, while the second early adult female participant has not received an apology from her mother. The first participant's forgiveness was assisted by an apology from the mother who was the abuser, while the second participant forgave on her own impulse without an apology from her biological mother. Of the four categories of forgiviness, these two participants were in the total forgiveness phase, where they managed to eliminate feelings of disappointment, hatred and anger at the violence they had experienced. Factors that influence such as family relationship status, religiosity and religious understanding. Meanwhile, inhibiting factors include focusing on parental guilt, feelings of hurt, deep sadness, painful experiences, unsupportive social environment, avoidance behavior, and negative judgment of parents.